Renting Apartments to Felons: Variations in Real Estate Agent Decisions due to Stigma. Issue 6 (3rd June 2017) - Furst, R. Terry; Evans, Douglas N.
ABSTRACT: The study provides a qualitative analysis of 300 real estate agent responses to telephone calls from researchers posing as convicted felons and inquiring about renting an apartment. Telephone calls were made to real estate agents in New York State and primarily in New York City. Criminal conviction type was manipulated across callers who revealed three types of prior convictions: child molestation, statutory rape, or drug trafficking. Analyses indicate that decisions about renting fall within a continuum of responses, including overt rejection, deferral of rental decision to landlords, ambivalence on the part of the agent, concerns about financial ability to pay rent, and concealing the caller's offense from the landlord. Reasons for acceptance and rejection of renting an apartment are explored. The stigmatized status of offenders appears to have contributed to the variations in the real estate agents responses.